Adverse effects of immune checkpoint inhibitor therapies on right ventricular function and pulmonary arterial dilatation. (February 2021) - Mylvaganam, Ruben; Avery, Ryan; Goldberg, Isaac; Makowski, Courtney; Kalhan, Ravi; Villaflor, Victoria; Cuttica, Michael J.
Immunologic risk factors contribute to endothelial dysfunction and development of pulmonary vascular disease. Immune checkpoint inhibitors, used as immunotherapies for malignancies, have a wide range of reported immune-related adverse events. We retrospectively describe the impact of immune checkpoint inhibitors on the development of pulmonary vascular injury and right ventricular dysfunction as compared across both computed tomography and transthoracic echocardiography. Twenty-four of 389 patients treated with immune checkpoint inhibitors at a single academic center between 2015 and 2019 were evaluated. Thirteen (54%) patients were treated with anti-programmed cell death receptor 1 (PD-1), 8 (33%) with anti-programmed death receptor ligand 1 (PD-L1) therapy, and 3 (13%) with combination anti-PD-1 and anti-cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4) therapy. At a median of 85 days of immune checkpoint inhibitor therapy, RVfwLS significantly increased from –20.6% to –16.7% ( p  = 0.002). After a median of 59 days of immune checkpoint inhibitor therapy, median pulmonary artery to aorta ratio worsened from 0.83 to 0.89 ( p  = 0.03). There was an correlation of duration of immune checkpoint inhibitor therapy (β = –0.574, p  = 0.003) with percent change in RVfwLS. Patients who received anti-PD-1 therapy (β = –0.796, p  = 0.001) showed the greatest correlation of duration of immune checkpoint inhibitor therapy with percent change in RVfwLS. Exposure to immune checkpoint inhibitors are associated with RV dysfunction and vascular changes as measured by strain and computed tomography, respectively.